(untitled) (International Journal of Language, Literacy and Translation, 2025)
The present paper is designed to shed light on the challenges of English-Arabic subtitling of a medical documentary series, the Pandemic: How to Prevent an Outbreak, broadcasted by Netflix in 2020. A descriptive quantitative paradigm was the method of the study, where the Arabic subtitling of the series was evaluated based on the scale of adequacy. The study also recognises the interdisciplinary knowledge that the translator (subtitler) should be equipped with to deal with the wide range of scientific terms in this series in order to achieve the desired goal. The study reveals several challenges; linguistically, grammatically, and culturally. The study also emphasises that ‘subtitlers’ should be perceptive to translation strategies in order to cope with these challenges. In conclusion, the findings suggest seminal solutions from different perspectives. One is to develop specialised training programmes by concerned institutions. The other, from technical perspective, suggests that technical terms without equivalents in Arabic should be put and illustrated for the viewer at the beginning in a split screen.